Judiciary efficiency and trade in tasks - Antonio Accetturo; Andrea Linarello; Andrea Petrella (European Regional Science Association (ERSA), 2015)
In this paper, we study how contract enforcement at the local level affects a firm's ability to supply customised intermediate inputs to foreign firms. Using Italian firm-level data, we show that firms located in courts with higher judicial trial length in civil disputes, which is our measure of contract enforcement, are less likely to supply customised inputs to foreign firms. The effect is stronger in contact-intensive sectors. In our empirical exercise we take advantage of two important characteristics of the Italian legal system. First, law determines the courts for disputes. This corresponds to the court where the plant is located. Trial length varies from less than one year in the most efficient court to more than seven years in the least efficient one. We observe large heterogeneity despite the fact that law should be uniformly applied over the country. Second, the Italian law codifies a specific contract type for the supply of customised intermediate inputs (contratto di subfornitura). This contract is widely used in the Italian context (Lazerson, 1999). In our data, firms report if they supply intermediate inputs to foreign customers under this type of contract. We deem it to be a very good approximation of the firm-to-firms relations in a Global value chain. We find that, when firms are located in inefficient courts, the probability to supply intermediate inputs abroad decreases. The effect are stronger for firms that operate in industries that are contract intensive. Following Nunn (2007), for each industry we measure contract intensity as the share of products that are not sold on organised markets according to the Rauch (1999) classification. We find that a standard deviation increase in trial length decreases the probability to supply customised inputs by 1.7 to 3 percentage points in industries at the 25th and 75th percentile of contract intensity, respectively.
Keywords: F10; F14; L14; 330; Local institutions; global value chains; local competitiveness